(3cGed GdUfGYI GdWHjIs - (3Ydj Hf YHGS GdeLhSj,fMh (B400 (3g`s ((3fGLi Hf UGdM s)
(3ChdgG (B:s
(3Chdg eHJhQ , hjHOC GdehLhO efg HGdHGH GdKGfi ai eOGhGI GdPHMI hGdNhGfjb bO PcQfG ai ZjQ gPG GdehVhY Cf GdPHMI hQe jYQV CeG ai GdMdb hCeG ai GdMfLQI s
(3BNQgG (B:s
(3BNQg eHJhQ jfJgi CKfGA GdHGH GdNeSjf ai eOGhGI NQhL GdHhd dZjQ EQGOI , heOGhGI GdPi jHhd ai GdaQGT hJRL CdhGf eNJdaI s
(3bWYI ef GdLRA GdKGfi GdYedi ef fSNI MGjI YTQs
(3UMM gPG GdcJGH Ydi fSNI bOjeI eTGHgI dg ai GdNW hJGQjNgG SfI (B435(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B317 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B162s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B194 ; (3eLdI eYgO GdeNWhWGJ (B- (3GdLRA (B5 - (3U (B328 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdWHs